Ultrasound-assisted catheter-directed thrombolysis versus anticoagulation alone for management of submassive pulmonary embolism. Issue 5 (November 2022) - Gorgis, Sarah; Mawri, Sagger; Dabbagh, Mohammed F.; Aurora, Lindsey; Ali, Mahmoud; Mitchell, Giordano; Jacobsen, Gordon; Hegab, Sara; Schwartz, Scott; Kelly, Bryan; Grafton, Gillian; Awdish, Rana; et al.
Abstract: Background: Patients with submassive pulmonary embolism (PE) are vulnerable to sudden deterioration, recurrent PE, and progression to pulmonary hypertension and chronic right ventricular (RV) dysfunction. Previous studies have suggested a clinical benefit of using ultrasound-assisted catheter-directed thrombolysis (USCDT) to invasively manage patients with submassive PE. However, there is sparse data comparing the clinical outcomes of these patients when treated with USCDT versus anticoagulation (AC) alone. We sought to compare the outcomes of USCDT versus AC alone in the management of submassive PE. Methods: 192 consecutive patients who underwent USCDT for submassive PE between January 2013 and February 2019 were identified. ICD9/ICD10 codes were used to detect 2554 patients diagnosed with PE who did not undergo thrombolysis. Propensity matching identified 192 patients with acute PE treated with AC alone. Clinical outcomes were compared between the two groups. Baseline demographics, laboratory values, and pulmonary embolism severity index scores were similar between the two cohorts. Results: There was a significant reduction in mean systolic pulmonary artery pressure (sPAP) in the USCDT group compared to the AC group (∆11 vs ∆3.9 mmHg, p  < 0.001). There was significant improvement in proportion of RV dysfunction in all patients, but the difference was larger in the USCDT group (∆43.3% vs ∆17.3%, p  < 0.001). Patients who underwent USCDT had lower 30-day (4.3% vs 10.5%, p  = 0.03), 90-day (5.5% vs 12.4%, p  = 0.03), and 1-year mortality (6.2% vs 14.2%, p  = 0.03). Conclusions: In patients with acute submassive PE, USCDT was associated with improved 30-day, 90-day, and 1 year mortality as compared to AC alone. USCDT also improved RV function and reduced sPAP to a greater degree than AC alone. Further studies are needed to verify these results in both short- and long-term outcomes. Graphical abstract: Unlabelled Image Highlights: Pulmonary embolism (PE) remains a significant cause of cardiovascular death. There is little data comparing ultrasound-assisted catheter-directed thrombolysis vs anticoagulation alone in submassive PE. Patients with submassive PE treated with USCDT had reduced long-term mortality. USCDT improved right ventricular function and reduced systolic pulmonary artery pressure to a greater degree than AC alone.